Factors Affecting Customer Satisfaction of Online Bookstore at Universitas Terbuka Indonesia - Iswanto , Yun; Susilo , Adhi (West African Journal of Open and Flexible Learning, 2026)
A number of factors presumed to contribute to customer satisfaction include logistical support, technological characteristics, information characteristics, homepage presentation, and product characteristics. This study aims to find out whether the logistics support, technological characteristics, characteristics of information, homepage presentation, and product characteristics influence customer satisfaction in e-commerce. This study was carried out in the Universitas Terbuka (UT) online bookstore. The research analysed 78 completed questionnaires from students as customers of UT’s online bookstore. Interviews also were conducted with students, regional office coordinators, and managers of UT’s online bookstore to get clarity of information and more in-depth data. The results of the correlation analysis indicated that the logistical support, information characteristics, homepage presentation, and product characteristics of UT’s online bookstore correlate with customer satisfaction. Interviews with regional office coordinators and online bookstore managers showed that UT has to do more orientation and promotion of online bookstore to students, and UT has to ensure the availability of books and prompt delivery.